Oil-soluble dyes for marking Spodoptera frugiperda (Lepidoptera: Noctuidae) - Vilarinho, Elis Cristine [UNESP]; Fernandes, Odair Aparecido [UNESP]; Omoto, Celso; Hunt, Thomas E. (Oxford University Press (OUP), 2006)
Although various biological aspects of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) have been examined, adult movement and dispersal of this insect pest is not well understood. Release-recapture techniques by using marked insects is a useful approach for dispersal studies; however, the marking technique should not significantly affect insect biology or behavior. Therefore, the effect of different concentrations of oil-soluble dyes (Solvent Blue 35 [C.I. 61554], Sudan Red 7B [C.I. 26050], Sudan Black B [26150], Sudan Orange G [C.I. 11920], and Sudan I 103624 [C.I. 12055]) on development, mortality, and fecundity of S. frugiperda was evaluated. Dyes were added to artificial diet used to feed larvae. Larval and pupal development and mortality, adult longevity, and female fecundity were evaluated. High concentrations (400 and 600 ppm) of all dyes led to longer larval and pupal stages. Adult life span and number of eggs were not affected by the dyes. Sudan Red 7B marked both adults and eggs very well. Solvent Blue 35 marked both adults and eggs, but the blue-marked eggs could not be distinguished from some bluish eggs laid by nonlabeled females. Adults and eggs were not adequately marked by the Sudan Black B, Sudan Orange G, and Sudan I 103624 (a yellow dye). © 2006 Entomological Society of America.
Keywords: Insect dispersal; Release-recapture; Resistance management